"Ofelia wędrowna" - bliżej twórczości Marii Komornickiej - Walęciuk-Dejneka, Beata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2012)
Review: Piotr Odmieniec Włast (Marya Komornicka), „Xięga poezji idyllicznej. Rzeczy Francuskie” (“Book of idyllic poetry. French things”), ed. Barbara Steligowska, transl. Joanna Majewska, Warsaw 2011, pp. 150. The review takes a closer look at the edition of poems left by Piotr Odmieniec Włast or Maria Komornicka edited by Barbara Stelingowska in Warsaw in 2011. “Xięga poezji idyllicznej. Rzeczy francuskie” („Book of idyllic poetry. French things”) collects texts in a foreign language along with translations done by Joanna Majewska. The review contains a short biographical outline of the poet revealing her dramatic life before nervous breakdown and after it. Moreover, it reviews the up-to-now editions of the texts included in the manuscript of “Xięga poezji idyllicznej” and presents the researchers who in the last years studied the life and output of Maria Komornicka. It also shows the edition of the poems on the basis of afterword and translator’s remarks inscribing the publication in the current of studies done from the perspective of feminist and cultural philosophy.
“Ofelia wędrowna” (“Wandering Ophelia”) – a closer look at Maria Komornicka’s output
Keywords: Komornicka Maria; Włast Piotr Odmieniec